Xerox Announces New Business Process Outsourcing Company Will Be Named "Conduent, Inc." (M2 Presswire, 2016)
This release contains "forward-looking statements" as defined in the Private Securities Litigation Reform Act of 1995. The words "anticipate," "believe," "estimate," "expect," "intend," "will," "should" and similar expressions, as they relate to us, are intended to identify forward-looking statements. These statements reflect management's current beliefs, assumptions and expectations and are subject to a number of factors that may cause actual results to differ materially.